First human case of severe septicaemia associated with Mycoplasma capricolum subsp. capricolum infection. Issue 5 (21st October 2015) - Heller, Martin; Schwarz, Rosemarie; Noe, Gerhard; Jores, Joerg; Fischer, Anne; Schubert, Evelyn; Sachse, Konrad
Abstract : Introduction: The bacterium Mycoplasma capricolum subsp. capricolum is known as a pathogen in goats. There have been no reports on a zoonotic potential so far. Case presentation: A case of septicaemia and meningoencephalitis in a 62-year-old patient has been associated with infection by M. capricolum subsp. capricolum . No other infectious agent could be detected. Conclusion: Although it was impossible to identify the source of infection, coincidental contact with small ruminants or consumption of food products from goats during a tourist trip may have played a role.